2018
DOI: 10.1016/j.envres.2018.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disrupting chemicals in seminal plasma and couple fecundity

Abstract: Growing evidence supports the importance of men's exposure to non-persistent endocrine disruptors (EDCs) and couple fecundability, as measured by time-to-pregnancy (TTP). This evolving literature contrasts with the largely equivocal findings reported for women's exposures and fecundity. While most evidence relies upon urinary concentrations, quantification of EDCs in seminal plasma may be more informative about potential toxicity arising within the testes. We analyzed 5 chemical classes of non-persistent EDCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Further, DEHP (4.20 µg/L) and DBP (2.06 µg/L) were reported at high concentrations in male seminal plasma from men in the US. The metabolites of DEHP (∑0.98 µg/L) and MBP (2.97 µg/L) also were present in considerable concentrations in seminal plasma in the same study [162]. These results suggested that phthalate metabolites can partition in seminal plasma.…”
Section: Biomonitoring Of Phthalatesmentioning
confidence: 70%
“…Further, DEHP (4.20 µg/L) and DBP (2.06 µg/L) were reported at high concentrations in male seminal plasma from men in the US. The metabolites of DEHP (∑0.98 µg/L) and MBP (2.97 µg/L) also were present in considerable concentrations in seminal plasma in the same study [162]. These results suggested that phthalate metabolites can partition in seminal plasma.…”
Section: Biomonitoring Of Phthalatesmentioning
confidence: 70%
“…These are manifested in the suppression of the growth of the testes and the development of secondary sexual characteristics in young male chickens. It has been shown that changes in the testes are visible not only in the seminiferous tubules but also in the interstitial tissue [ 53 , 54 ]. Studies carried out on two groups of male rats receiving DDT with food at doses of 50 and 100 mg/kg of body weight showed dose-dependent decreases in the testes and sperm motility [ 55 ].…”
Section: History Of Investigations On Affection Of the Adrenal Glands By Subtoxic And Toxic Doses Of Ddtmentioning
confidence: 99%
“…Human exposure to TCC may also be due to daily supplies, drinking water and dust [ 26 ]. As a result, its detection is frequent in human tissue, such as fingernails and body fluids, including blood, urine and seminal plasma [ 40 , 41 , 42 , 43 ], thus causing a potential hazard to human health. It is noteworthy that TCC may represent a risk for children, as it has been recently found in urine of Brazilian children and its use also seems to be associated to DNA damage [ 44 ].…”
Section: Introductionmentioning
confidence: 99%